From Public Monopsony to Competitive Market: More Efficiency but Higher Prices - Josse Delfgaauw; Robert Dur (Center for Economic Studies and ifo Institute (CESifo), 2003)
This paper examines the consequences of creating a fully competitive market in a sector previously dominated by a cost-minimising public firm. Workers in the economy are heterogeneous in their motivation to work in the sector. In line with empirical findings, our model implies that firms in the competitive market provide stronger monetary incentives to workers, reach higher productivity, and employ less workers than the public firm. Allocative efficiency therefore increases. Nevertheless, prices of the sector's output rise as competition between private firms for the best motivated workers leads to higher wage cost than under the public monopsony. Political support for liberalisation may therefore be limited.
Keywords: H40; J30; J40; L20; L30; L50; 330; liberalisation; monopsony power; incentive wages; intrinsic motivation